2019
DOI: 10.3906/sag-1902-106
|View full text |Cite
|
Sign up to set email alerts
|

Twenty children with non-Wilms renal tumors from a reference center in Central Anatolia, Turkey

Abstract: Background/aim: Non-Wilms renal tumors (NWRTs) are rarely encountered in children. The aim of this study is to determine the treatment strategies, prognosis, outcomes, and survival of children with NWRTs at Erciyes University in Kayseri, Turkey. Materials and methods: Medical records of all patients (n = 20) treated for NWRTs over a 23-year period (1995-2018) were reviewed retrospectively. Results: There was male predominance (female/male: 7/13); the median age at diagnosis was 3.2 years old (0.1-13.5 years ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…NWRTs that occur in children include CMN, CCSK, RCC, MRTK, lymphoma, angiomyolipoma, and other rare entities [2]. Different studies have reported that the proportion of NWRTs in renal tumors varies from 13.6-18.7% [3][4]. Preoperative imaging, which can be performed to determine the anatomic location and extent of the mass, is often su cient to presume a diagnosis [12].…”
Section: Discussionmentioning
confidence: 99%
“…NWRTs that occur in children include CMN, CCSK, RCC, MRTK, lymphoma, angiomyolipoma, and other rare entities [2]. Different studies have reported that the proportion of NWRTs in renal tumors varies from 13.6-18.7% [3][4]. Preoperative imaging, which can be performed to determine the anatomic location and extent of the mass, is often su cient to presume a diagnosis [12].…”
Section: Discussionmentioning
confidence: 99%
“…NWRTs that occur in children include CMN, CCSK, RCC, MRTK, lymphoma, angiomyolipoma, and other rare entities [ 2 ]. Different studies have reported that the proportion of NWRTs in renal tumors varies from 13.6 to 18.7% [ 3 , 4 ]. In our single center, pediatric NWRTs comprise 19.1% of all renal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…surveyed 20 children with nonWilm's tumors in Turkey and reported the case of a 2.5-month-old girl infant with bilateral renal PNET. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%
“…Major differentials to be considered for small round cell tumors from kidney, all with similar morphological features, include malignant lymphoma, rhabdomyosarcoma, renal neuroblastoma, Wilms' tumor, small-cell osteosarcoma, desmoplastic small-cell tumor, synovial sarcoma, small-cell neuroendocrine carcinoma, and PNET. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%